Future of robotic surgery in urology - Rassweiler, Jens (BJU international, 2017)
Objectives To provide a comprehensive overview of the current status of the field of robotic systems for urological surgery and discuss future perspectives. Materials and Methods A non?systematic literature review was performed using PubMed/Medline search electronic engines. Existing patents for robotic devices were researched using the Google search engine. Findings were also critically analysed taking into account the personal experience of the authors. Results The relevant patents for the first generation of the da Vinci platform will expire in 2019. New robotic systems are coming onto the stage. These can be classified according to type of console, arrangement of robotic arms, handles and instruments, and other specific features (haptic feedback, eye?tracking). The Telelap ALF?X robot uses an open console with eye?tracking, laparoscopy?like handles with haptic feedback, and arms mounted on separate carts; first clinical trials with this system were reported in 2016. The Medtronic robot provides an open console using three?dimensional high?definition video technology and three arms. The Avatera robot features a closed console with microscope?like oculars, four arms arranged on one cart, and 5?mm instruments with six degrees of freedom. The REVO?I consists of an open console and a four?arm arrangement on one cart; the first experiments with this system were published in 2016. Medicaroid uses a semi?open console and three robot arms attached to the operating table. Clinical trials of the SP 1098?platform using the da Vinci Xi for console?based single?port surgery were reported in 2015. The SPORT robot has been tested in animal experiments for single?port surgery. The SurgiBot represents a bedside solution for single?port surgery providing flexible tube?guided instruments. The Avicenna Roboflex has been developed for robotic flexible ureteroscopy, with promising early clinical results. Conclusions Several console?based robots for laparoscopic multi? and single?port surgery are expected to come to market within the next 5 years. Future developments in the field of robotic surgery are likely to focus on the specific features of robotic arms, instruments, console, and video technology. The high technical standards of four da Vinci generations have set a high bar for upcoming devices. Ultimately, the implementation of these upcoming systems will depend on their clinical applicability and costs. How these technical developments will facilitate surgery and whether their use will translate into better outcomes for our patients remains to be determined.
Gesehen am 03.04.2018